Regional Disparity in Physical Resources in the Health Sector in Iran: A Comparison of Two Time Periods - Ali AKBARI-SARI; Satar REZAEI; Enayatollah HOMAIE-RAD; Nasim DEHGHANIAN; Yousef CHAVEHPOUR (Tehran University of Medical Sciences, 2015)
Background: One of the major health policy issues, in the both developed and developing countries, is the equality in the distribution of health resources. The aim of this study was to investigate the disparity in the distribution of health physical resources across the provinces of Iran in 2001 and 2011. Methods: This was a cross-sectional retrospective study which investigated inequality in the distribution of health physical resources by three indexes of Gini Coefficient, Gaswirth index and Index of Dissimilarity. The data on prov-inces were obtained from the yearbook statistics and Ministry of Health, and Medical Education. The Excel software was used to calculated indexes. Results: The finding showed the mean Gini Coefficient for all variables was 0.178 in 2001 and 0.158 in 2011. Besides, the mean Gaswirth index and index of dissimilarity were 11.5 and 1.5% in 2001 and 11 and 1.4% in 2011, respectively. Conclusion: There was slightly inequality in distribution of physical health resources in Iran. According to the results of three indexes, this study showed when Tehran province excluding from total sample, the inequality was decreased.